BUILDING CULTURE – IS IT POSSIBLE IN EU-FUNDED PROJECTS? (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The focus of the study is on the environment, which is an essential part of the history, culture and economy of each country. The surrounding environment also serves as an important means of artistic expression, creating a sense of belonging, identity and tomorrow's heritage. The impact of the environment on society is crucial in ensuring and improving the quality of life. The surrounding environment is influenced by social and political factors, economic development and culture affect the surrounding environment. At the same time, these factors are also influenced by the environment itself, creating continuous and mutual interaction. Economic interests drive the development of construction in a market environment, but the quality of construction works, and the quality of the environment associated with it are public goods, the improvement of which may not be a business goal. Construction policy determines the priorities and strategic goals of the government. In this way, the state protects the public good. Every human activity aimed at creating, preserving or transforming the surrounding environment includes the aspect of creating culture, cultural identity and diversity. Construction culture requires not only the preservation of existing buildings with cultural and historical significance, but also the responsible creation of new public spaces. The novelty of this research lies in its examination of how construction culture principles are integrated into the implementation of European Union (EU) Cohesion Policy Fund projects—an aspect that has not been systematically analyzed before. This study bridges the gap between construction policy, cultural identity, and sustainable urban development by assessing whether EU-funded projects uphold the values of construction culture. The aim of the study is to determine whether the principles of construction culture can be observed in the implementation of European Union (EU) Cohesion Policy Fund projects. To achieve this goal, the following research tasks have been set: to analyze the concept of construction culture; to identify the main principles of culture formation and to provide recommendations for observing these principles when implementing EU Cohesion Policy Fund projects. The monographic and descriptive method and the logically constructive method are used. The results have developed the main components necessary for ensuring construction culture. Main conclusions and recommendations: considering the significant investments of EU funds in infrastructure and their impact on the economy and welfare of the Member States, the construction sector with all its sub-sectors should be given much greater attention. Investments in research and development of this sector should be increased in order to respond to the changing and growing demands of society, ensuring the competitiveness of the sector both in the EU and globally.